An Irradiance‐Adaptable Near‐Infrared Vertical Heterojunction Phototransistor (Adv. Mater. 40/2022). Issue 40 (6th October 2022) - Zhang, Mengyu; Chi, Zhiguo; Wang, Guoqing; Fan, Zelong; Wu, Honglei; Yang, Ping; Yang, Junbo; Yan, Peiguang; Sun, Zhenhua
Abstract : Phototransistors In article number 2205679, Peiguang Yan, Zhenhua Sun, and co‐workers report a near‐infrared phototransistor with benign light‐irradiance adaptability using a vertically stacking graphene/lead sulfide quantum dots/graphene heterojunction as the conductive channel. The dynamic trapping and detrapping processes in the quantum dot film enable the inhabitation or potentiation of the photoresponse, based on which the photopic or scotopic adaptation behavior of the human retina is successfully mimicked, respectively.